The Effectiveness of Group Counseling using Self-Management Techniques to Reduce Nomophobia in Vocational Students - Firdawati, Andi; Sinring, Abdullah; Buchori, Sahril (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aimed to examine the effectiveness of self-management techniques in reducing nomophobic behavior in vocational students. The research method used Single Subject Research (SSR) design with an A-B-A model. This research was conducted in 2024; the research subjects were students who experienced high levels of nomophobia. Data were collected through direct observation of smartphone use behavior, with visual analysis of changes during the baseline phase, intervention, and after the intervention was stopped. The results showed a significant decrease in the subject's level of nomophobia during the intervention phase and stability of behavior change after the intervention was completed. In conclusion, the study found that self-management techniques can be effectively implemented in intervention programs to reduce smartphone dependence, especially among adolescents. The contribution of this study is to provide practical guidance for teachers, school counselors, or other educational personnel in helping students who experience nomophobia through self-management techniques.